Potential Caves: Inventory of Subsurface Access Points on the Surface of Titan. Issue 11 (22nd November 2022) - Malaska, Michael J.; Schoenfeld, Ashley; Wynne, J. Judson; Mitchell, Karl L.; White, Oliver; Howard, Alan; Moore, Jeffrey; Umurhan, Orkan
Abstract: We propose that cycling hydrocarbon rains on Saturn's moon Titan are likely to create subsurface conduits through dissolution geology of the extensive organic and largely‐soluble substrate. In this work we inventory different terrains and locations on Titan that could host potential subsurface access points or caves. Using Cassini data, we identified and enumerated a cryovolcanic construct, filled and empty lake basins that may have formed through karstic processes, estimates of closed valleys in organic plateaux, and enigmatic equatorial pits. Our preliminary survey identified over 21, 000 estimated locations for future exploration to identify potential caves and cave forming processes on that world. We speculate that the exploration of these caves could teach us about the cave forming processes, as well as the past climate history and perhaps even chemical deposition history on Titan. Plain Language Summary: Saturn's moon Titan may have extensive caves resulting from cycling hydrocarbon rains dissolving extensive organic materials. Using Cassini data, we identified over 21, 000 potential locations on the surface where caves might exist. By exploring Titan caves, we could learn about dissolution geology, past Titan climate, and even how organic molecule production on Titan has changes over time. Titan caves present an exciting exploration target. Key Points: We mapped locations with potential subsurface access points (caves) on Titan We identified over 21, 000 locations that could contain caves Caves on Titan could form from dissolution geology/karstic processes